Biodiversity conservation corridors initiative (BCI) report 2006-2011 (Asian Development Bank, 2011)
Contents: The biodiversity conservation corridors initiative in the GMS; Achievements, impacts and lessons learned from BCI pilot sites 2006-2010; Scaling up BCI investments in Cambodia, Lao DR and Viet Nam; The way forward with CEP-BCI phase II.